Dokumenter Kesultanan Jambi, Titah dan Singgasana dengan Gaya Expository - Muhammad Anton Ghunarso; Hery Sasongko; Muhammad Hamdanu Syakirin (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The Jambi Sultanate was one of the Malay sultanates that played a significant role in the history of the Indonesian archipelago; however, its existence has been nearly forgotten from the collective memory of the Jambi people due to a 117-year power vacuum following the death of Sultan Thaha Syaifuddin in 1904 and the formal dissolution of the sultanate by Dutch colonial authorities in 1906. This historical void subsequently gave rise to conflict in the form of illegitimate sultan claimants whose actions caused harm to indigenous communities. The documentary film Kesultanan Jambi, Titah dan Singgasana (The Jambi Sultanate: Royal Decree and the Throne) was created to address these issues while presenting their resolution through a rigorous academic research process that successfully identified the original royal regalia and confirmed Sultan Sayyid Fuad Abdurrahman as the legitimate 21st heir of the Jambi Sultanate, who was formally installed through a traditional enthronement ceremony on 28 July 2022. The expository mode was chosen for its capacity to deliver historical information in a structured and argumentative manner through voice of God narration, which functions simultaneously as an introducer, an informer, and an interpreter, while academic sources serve as scientific validators of the narrative's claims. This 21-minute-7-second film is intended to serve as an educational medium for the people of Jambi, particularly the younger generation, regarding the history and cultural identity of the Jambi Sultanate in the present day.